THE EVALUATION OF STUDENT CARE AND SUPPORT SYSTEM PROJECT OF BANSUNYOONG SCHOOL UNDER THE OFFICE OF NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Naosuwan, Sopa; Dhammatikul , Akara; Chatakan , Werayut; Promnil, Pramote (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research article were: 1) to investigate the system assessment, 2) to investigate program planning, 3) to investigate program implementation, 4) to investigate program improvement, and 5) to investigate program certification of student care and support system project of Bansanyoong school under the office of Nakhon Si Thammarat primary educational service area office 1. The sample consisted of 52 people including 1 director, 9 teachers, 18 students and 24 parents. The tools used for this data collection consisted of 3 questionnaires, namely 1) project system assessment questionnaire and program planning 2) implementation assessment 3) project improvement questionnaire and assessment questionnaire for project acceptance and 4) In-Dept Interviews. The statistics employed for data analysis were percentage, mean and standard deviation The research results were as follows: 1) The overall project system assessment of the student care and support system project at Bansanyoong School indicates that the evaluation results are at the highest level. 2) The overall project planning assessment of the student care and support system project at Bansanyoong School indicates that the evaluation results are at the highest level. 3) The overall project implementation of the student care and support system project at Bansanyoong School indicates that the evaluation results are at the highest level. 4) The overall project improvement of the student care and support system project at Bansanyoong School indicates that the evaluation results are at a high level. Most teachers lack the knowledge and understanding of in-depth mentoring, and teachers who are given the opportunity to make mistakes around the project must strictly follow up with their work, and the teacher used inappropriate language with the students so there were sad. 5) The overall project acceptance of the student care and support system project at Bansanyoong School indicates that the evaluation results are at the highest level.